Active chromatin marks are retained on X chromosomes lacking gene or repeat silencing despite XIST/Xist expression in somatic cell hybrids. - Nancy P Thorogood; Carolyn J Brown (PLoS ONE, 2010)
X-chromosome inactivation occurs early in mammalian development and results in the inactive X chromosome acquiring numerous hallmarks of heterochromatin. While XIST is a key player in the inactivation process, the method of action of this ncRNA is yet to be determined.To assess which features of heterochromatin may be directly recruited by the expression and localization of the XIST RNA we have analyzed a mouse/human somatic cell hybrid in which expression of human and mouse XIST/Xist has been induced from the active X by demethylation. Such hybrids had previously been demonstrated to disconnect XIST/Xist expression from gene silencing and we confirm maintenance of X-linked gene expression, even close to the Xist locus, despite the localized expression of mouse Xist.Loss of the active chromatin marks H3 acetylation and H3 lysine 4 methylation was not observed upon XIST/Xist expression, nor was there a gain of DNA methylation; thus these marks of facultative heterochromatin are not solely dependent upon Xist expression. Cot-1 holes, regions of depleted RNA hybridization with a Cot-1 probe, were observed upon Xist expression; however, these were at reduced frequency and intensity in these somatic cells. Domains of human Cot-1 transcription were observed corresponding to the human chromosomes in the somatic cell hybrids. The Cot-1 domain of the X was not reduced with the expression of XIST, which fails to localize to the human X chromosome in a mouse somatic cell background. The human inactive X in a mouse/human hybrid cell also shows delocalized XIST expression and an ongoing Cot-1 domain, despite X-linked gene silencing. These results are consistent with recent reports separating Cot-1 silencing from genic silencing, but also demonstrate repetitive element expression from an otherwise silent X chromosome in these hybrid cells.